Current Approaches to the Treatment of Diarrhea in Children - О.S. Niankovska (Zaslavsky O.Yu., 2015)
This article considers the current approaches to the treatment of acute diarrhea, taking into account the ESPGHAN guidelines (2014), which involves the use of oral rehydration therapy, zinc at a dose of 10 mg/day in children under 6 months, in children older than 6 months - 20 mg/day for 10-14 days, probiotics, antisecretory and antiemetic drugs, adsorbents and antibiotics.